USM APPRECIATES STAFF MEMBERS WHO WORK DURING FESTIVE HOLIDAYS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 17 July 2015 Universiti Sains Malaysia (USM) appreciates and values its staff members who work during festive holidays such as Hari Raya Aidil Fitri. Its ViceChancellor Professor Dato' Dr. Omar Osman said, the University truly appreciates the sacrifices of more than 500 doctors and nurses on duty at USM Hospital in Kubang Kerian every day including those oncall and more than 60 security personnel guarding the campuses while other university’s staff get to return to their hometowns and celebrate Aidilfitri with their families.